HUBUNGAN PANJANG PUNTUNG DAN INDEKS MASSA TUBUH DENGAN KESEIMBANGAN BERJALAN PADA PASIEN PASCA AMPUTASI ANGGOTA GERAK BAWAH - Muhammad Syaifuddin (JURNAL ILMIAH MOMENTUM, 2016)
Amputation can be interpreted as separating the some part or all extremities. Lower limb amputation reaches 85-90 % from all amputations and below-knee amputation ( transtibial amputation ) is the most amputation that has been done. The loss of the lower lead to the undermining of limb funtion, as balance funtion and confidence.The study was observational analytic research with cross sectional design. The research location was in Kuspito, Karanganyar Jaten. The  sample were 52 patients with lower limb amputation, uses comparative study of means. The techniques to collect data used questionnaires and literature. Analysis of data used linear regression .There was a positive correlation was statistically significant between the length of the stump ( b1 = 0.49 ; 95 % CI ; 0.15 to 0.84 ; p = 0.006 ) and IMT ( b2 = 0.31 ; CI 95 % ; 0 , 09 to 0.53; p = 0.006 ) with the balance to walk.Long stump ( stump ) and body mass index ( BMI ) was associated with a walking balance. Keywords: long butt ( stump), IMT , walking balance.